Effect of sacubitril/valsartan and empagliflozin on systemic inflammation and scar remodeling in a swine model of myocardial infarction. (3rd October 2022) - Martinez-Falguera, D; Monguio-Tortajada, M; Ferrer Curriu, G; Aranyo, J; Teis, A; Fadeuilhe, E; Rodriguez-Leor, O; Diaz-Guemez, I; Courageux, Y; Roura, S; Bayes-Genis, A; Bisbal, F; et al.
Abstract: Background: Angiotensin receptor neprilysin inhibitor (ARNI) and sodium glucose cotransporter 2 inhibitors (SGLT2i) lead to reduced cardiovascular death and hospitalization rates for heart failure, but mechanisms of action remain unclear. Purpose: To evaluate the effect of ARNI and SLGT2i on cardiac function, systemic inflammation and scar remodeling in a porcine model of acute myocardial infarction (MI). Methods: Thirty-three pigs (18 female, 15 male) with non-revascularized MI were randomized to receive treatment with beta-blocker (BB) only (BB group, n=8), empagliflozin + BB (SGLT2i group, n=8), sacubitril/valsartan + BB (ARNI group, n=9) or empagliflozin + sacubitril/valsartan + BB (SGLT2i + ARNI group, n=8) for 30 days post-MI. Cardiac function parameters were studied at 2- and 30-days post-MI by cardiac magnetic resonance imaging. The systemic immune response was analysed at baseline, 2-, 15- and 30-days post-MI to estimate 1) the absolute number of neutrophils and lymphocytes by FSC-A/SSC-A, 2) the circulating monocytes (CD172a+) and their phenotype according to CD73+, and CCR2+ expression. Animals were euthanized at 30 days, interstitial collagen and vascular density of the scar were quantified. Results: Left ventricular ejection fraction (LVEF) and stoke volume (LVSV) improved in SGLT2i + ARNI group (P=0.02, P=0.002, respectively, 2 vs 30 days post-MI). Right ventricular ejection fraction (RVEF) and stroke volume (RVSV) improved in ARNI treatment arm (P=0.03; P=0.02, respectively, 2 vs 30 days post-MI). Significant increase in LV mass was only observed in BB group (P=0.02; 2 vs 30 days post-MI). SGLT2i and ARNI treatment prevented the acute increase in circulating leukocytes 2 days post-MI (P=0.0095; P=0.0091, respectively). Moreover, SGLT2i reduced the CCR2+ activated monocytes count at 15 days post-infarction (P=0.01). In contrast, the combined treatment increased the number of circulating monocytes (CD172a+) at 30 days (P=0.008). Reduced collagen I (P=0.04), and Col I/Col III ratio (P=0.02) was observed in ARNI group, and higher collagen III content (P=0.02) in SGLT2i group. Vascular density was significantly increased in SGLT2i + ARNI group (P=0.03). Conclusions: SGLT2i modulates systemic inflammatory state. ARNI reduces myocardial fibrosis and improves right ventricular function. Combined treatment improves vascular density and left cardiac function in a post-MI porcine model. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Boehringer Ingelheim Spain, S.A, and Instituto de Salud Carlos III, CIBER Cardiovascular